Efektivitas Governansi Digital dalam Pelayanan Administrasi Kependudukan melalui Aplikasi LAPAK SARAH: Studi Perubahan Data pada Kartu Keluarga di Desa Dayu, Kecamatan Nglegok, Kabupaten Blitar (Pusat Riset dan Inovasi Nasional, 2026)
Population administration services are essential public services that fulfill the civil rights of the community. However, the process of changing Family Card (KK) data at the village level often faces problems, such as complicated procedures and limited access to services. With the development of information technology, village governments are required to implement digital-based service innovations through a digital governance approach. This study aims to evaluate the effectiveness of digital governance implementation in population administration services through the LAPAK SARAH application for Family Card data changes in Dayu Village, Nglegok District, Blitar Regency. The approach used in this study is descriptive qualitative with data collection techniques in the form of in-depth interviews, observation, and documentation. Research informants included village officials and community members as service users. The results showed that the use of the LAPAK SARAH application could improve the performance of population administration services, as indicated by faster service times, easier access, and increased service transparency and accountability. From a digital governance perspective, the role of village officials, cooperation with the Population and Civil Registration Office, and community participation improved service quality. However, this study also found obstacles such as limited digital literacy among the community, differences in village device capacity, and technical infrastructure constraints. The success of digital population administration services at the village level is not only determined by the use of technology, but also by the quality of governance and the readiness of the parties involved.